2018
DOI: 10.1111/jopy.12377
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and stability of narrative coherence: An examination of personal narrative as a domain of adult personality

Abstract: The ways in which we tell autobiographical narratives reflect a stable feature of individual differences. Further, they suggest that this stable element of personality is necessary, but not sufficient, in accounting for specific event and life narrative coherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…The present study sheds an interesting light on the construct of memory coherence and its relation to psychological well-being and psychopathology. Developmental research has demonstrated that memory coherence can be considered an individual difference factor, with some individuals generally being more capable of constructing coherent memories than others [10,64,65]. In line with this notion of memory coherence as a cognitive skill, is the observation that individuals' memory coherence is consistent over time and across memories [64,65].…”
Section: Plos Onementioning
confidence: 91%
See 2 more Smart Citations
“…The present study sheds an interesting light on the construct of memory coherence and its relation to psychological well-being and psychopathology. Developmental research has demonstrated that memory coherence can be considered an individual difference factor, with some individuals generally being more capable of constructing coherent memories than others [10,64,65]. In line with this notion of memory coherence as a cognitive skill, is the observation that individuals' memory coherence is consistent over time and across memories [64,65].…”
Section: Plos Onementioning
confidence: 91%
“…Developmental research has demonstrated that memory coherence can be considered an individual difference factor, with some individuals generally being more capable of constructing coherent memories than others [10,64,65]. In line with this notion of memory coherence as a cognitive skill, is the observation that individuals' memory coherence is consistent over time and across memories [64,65]. In addition to being a cognitive skill, research has indicated that memory coherence is dependent on specific characteristics of the event being narrated upon, such as valence, intensity, and time passed since occurrence of the event.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation comes from fact that narrative coherence does not merely originate from individual-specific variables, but also from event-and narration-specific variables (Waters et al, 2019). We chose to work with a narrative task on turning point memories, since research has shown that it are in particular those memories that are relevant for identity that are likely to serve memories' social functions (Waters & Fivush, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, this might account for the absence of any direct effects of social anxiety on narrative coherence. Future research could work with everyday conversations topics or more mundane event memories, as those might be harder to narrate coherently about for socially anxious people, allowing for more inter-individual variability in coherence (Waters et al, 2019). Another distinction could be made in future research between the recall of social vs non-social memories.…”
Section: Discussionmentioning
confidence: 99%